Peran Notaris dalam Mendorong Terciptanya Kepastian Hukum Bagi Investor dalam Investasi Asing - Yusrizal Yusrizal (Universitas Islam Indonesia, 2018)
This study discusses how the role of the notary in encouraging the legal certainty investors in foreign investment with the aim of knowing the extent of the role of the notary in serving foreign investors. This study uses a combination of normative and empirical methods by examining some rules and interviews. The results of the study found that the role of the notary on this issue is limited to making a Company Establishment Deed, Cooperation Agreement, Minutes of General Meeting of Shareholders Substitution of Shareholders, investors can also provide power of attorney to the notary related to the permit management. In all types of notary authority there are also legal consequences for the notary when negligence in making the deed in the form of civil and administrative sanctions.